Treatment with the Prolyl Hydroxylase Inhibitor JNJ Promotes Abdominal Aortic Aneurysm Progression in Diabetic Mice. (March 2022) - Guo, Jia; Shoji, Tahakiro; Ge, Yingbin; Zheng, Xiaoya; Li, Yankui; Zhao, Sihai; Ikezoe, Toru; Liu, Shuai; Huang, Jianhua; Wang, Wei; Xu, Baohui; Dalman, Ronald L.
Abstract : Objective: Prolyl hydroxylase domain containing proteins (PHD) rigorously regulate intracellular hypoxia inducible factor-1 (HIF-1) protein expression and activity. Diabetes impairs PHD activity and attenuates abdominal aortic aneurysm (AAA) progression. The extent to which dysregulated PHD activity contributes to diabetes mediated AAA suppression remains undetermined. Methods: AAAs were induced in diabetic and non-diabetic male C57BL/6J mice via intra-aortic elastase infusion. A PHD inhibitor (JNJ-42041935, aka "JNJ", 150 mmol/kg) or vehicle alone was administered daily starting one day prior to AAA induction for 14 days. Influences on AAA progression was assessed via ultrasonography and histopathology. Expression of aortic HIF-1α, three of its target genes and macrophage derived mediators were assayed via quantitative reverse transcription polymerase chain reaction. Aneurysmal sections from AAA patients with and without diabetes (two patients in each group) were immunostained for HIF-1α and vascular endothelial growth factor (VEGF)-A. Results: Expression of HIF-1α target genes (erythropoietin, VEGF-A, and glucose transporter-1) was reduced by 45% – 95% in experimental diabetic aortas. Diameter enlargement was similarly limited, as were mural elastin degradation, leukocyte infiltration, and neo-angiogenesis (reduced capillary density and length) on histopathology. Pre-treatment with JNJ prior to AAA initiation augmented aortic HIF-1α target gene expression and aneurysm progression in diabetic mice, along with macrophage VEGF-A and matrix metalloproteinase 2 mRNA expression. No differences were noted in HIF-1α or VEGF-A expression on aortic immunohistochemical staining of human aortic tissue as a function of diabetes status. Conclusion: Small molecule PHD inhibitor treatment reduces or offsets impairment of experimental AAA progression in hyperglycemic mice, highlighting the potential contribution of dysregulated PHD activity to diabetes mediated aneurysm suppression.